Language Phenomena in Pro-Palestinian Posts on Social Media - Mualafina, Rawinda Fitrotul; Ulfiyani, Siti (Universitas PGRI Semarang, 2025)
This research aims to describe a number of language phenomena that appear in posts on social media related to the pro-Palestinian movement. This research is a qualitative descriptive study. The data sources for this research are the social media platforms Instagram, X, and Telegram. The data in this research consists of linguistic elements in pro-Palestinian posts on the social media platforms Instagram, X, and Telegram. The data obtained are analysed using the matching method. The results of the data analysis are presented informally.Â Data was collected using listening and note-taking techniques with data sources in the form of social media, especially Instagram, X, and Telegram. The result obtained include that pro-Palestinian movements or action produce a number of language phenomena, including the emergence of registers, slang, and dysphemism in posts on social media. The results illustrate the emergence of a linguistic phenomenon arising from a social phenomenon currently occurring in society. As part of the social element, language once again demonstrates the distinctiveness of certain groups based on the linguistic codes that have developed. Furthermore, the emerging language phenomenon does not merely appear as a form of vocabulary or language codes. Indirectly, these language codes manifest as a form of support and even resistance echoed by the public against the injustice currently happening to the Palestinian people.